The Management of Vietnam's Border Disputes: What Impact on Its Sovereignty and Regional Integration? - AMER, RAMSES (Contemporary Southeast Asia, 2005)
The main aim of this article is to study Vietnam's border disputes, the way they have been and are being managed and the challenges that the remaining disputes pose. It also assesses the impact of Vietnam's border disputes on Vietnam's sovereignty, as well as the impact of the border disputes on Vietnam's regional integration. The study focuses on developments since the early 1990s. The progress in managing and resolving Vietnam's border disputes is outlined. The remaining unresolved disputes are analysed and the challenge they pose is discussed. The degree of success in managing Vietnam's border disputes is examined through the pattern of negotiations involving Vietnam and its neighbours. The impact of the border disputes on Vietnam's sovereignty is studied from two main perspectives: the first relates to how unresolved border disputes affect Vietnam's sovereignty, in particular, Vietnam's capability in efficiently exercising its sovereignty; the second deals with the impact of the agreements reached on border disputes on Vietnam's sovereignty. The regional integration dimension is studied primarily from the perspective of how Vietnam contributes to the enhancement of the conflict management approach of the Association of Southeast Asian Nations (ASEAN).